Rapid divergence of mussel populations despite incomplete barriers to dispersal. Issue 7 (26th April 2018) - Maas, Diede L.; Prost, Stefan; Bi, Ke; Smith, Lydia L.; Armstrong, Ellie E.; Aji, Ludi P.; Toha, Abdul Hamid A.; Gillespie, Rosemary G.; Becking, Leontine E.
Abstract: Striking genetic structure among marine populations at small spatial scales is becoming evident with extensive molecular studies. Such observations suggest isolation at small scales may play an important role in forming patterns of genetic diversity within species. Isolation‐by‐distance, isolation‐by‐environment and historical priority effects are umbrella terms for a suite of processes that underlie genetic structure, but their relative importance at different spatial and temporal scales remains elusive. Here, we use marine lakes in Indonesia to assess genetic structure and assess the relative roles of the processes in shaping genetic differentiation in populations of a bivalve mussel ( Brachidontes sp.). Marine lakes are landlocked waterbodies of similar age (6, 000–10, 000 years), but with heterogeneous environments and varying degrees of connection to the sea. Using a population genomic approach (double‐digest restriction‐site‐associated DNA sequencing), we show strong genetic structuring across populations (range F ST : 0.07–0.24) and find limited gene flow through admixture plots. At large spatial scales (>1, 400 km), a clear isolation‐by‐distance pattern was detected. At smaller spatial scales (<200 km), this pattern is maintained, but accompanied by an association of genetic divergence with degree of connection. We hypothesize that (incomplete) dispersal barriers can cause initial isolation, allowing priority effects to give the numerical advantage necessary to initiate strong genetic structure. Priority effects may be strengthened by local adaptation, which the data may corroborate by showing a high correlation between mussel genotypes and temperature. Our study indicates an often‐neglected role of (evolution‐mediated) priority effects in shaping population divergence.